Synthesis of macro porous ceramic materials - M. A., Azmah Hanim (Springer, 2021)
This chapter explored the synthesis method of macro porous ceramic by using the partial sintering, direct foaming, replica template and sacrificial template technique. The focus is to produce macro porosity in the ceramic for specific application purposes that required this porosity range. At first, fundamentals in each technique were discussed and the advancement in the topic for the recent five years was presented. This is followed by advantages and limitations existing with the current technology for each synthesizing technique. Finally, the chapter covers the possible future trends that can be explored in making the process of synthesizing macro porous ceramic to be more repeatable, stable and sustainable in the near future.